Integrasi Kearifan Lokal Kampung Budaya Batu Urip dalam Pembelajaran Sejarah untuk Penguatan Materi Sejarah Lokal - Agus Susilo; Sariyatun; Muhammad Akhyar (JOEAI (Journal of Education and Instruction), 2025)
This study aims to integrate the local wisdom of Kampung Budaya Batu Urip into history learning to strengthen local historical content in schools. The method used is a qualitative approach with a case study design. Data were collected through observation, in-depth interviews with teachers and community figures, and documentation, then analyzed using thematic analysis techniques to explore the integration of local values into teaching practices. The results show that Kampung Budaya Batu Urip holds great potential as a history learning resource, reflecting values such as struggle, mutual cooperation, and cultural preservation. The integration of local wisdom into history learning enhances student engagement, strengthens cultural identity, and expands contextual understanding of historical events. In conclusion, integrating the local values of Kampung Budaya Batu Urip into history learning not only strengthens the relevance of the material but also supports character development and fosters more contextual and meaningful learning.   Keywords: Batu Urip, History Learning, Local Knowledge, Learning Resource